Evaluating Consumer Preferences for Sustainable Products: A Comparative Study Across Five Countries - Marko Šostar; Vladimir Ristanović (World)
In times of global natural changes, environmental pollution, and the harmful impacts of certain products, it is essential to observe consumer behavior regarding preferences for products with sustainable characteristics. This paper evaluates the process of making decisions about the purchase of sustainable products using the Analytical Hierarchy Process (AHP), as the most common method of multi-criteria decision-making. The aim of the research is to define the influences that change consumer behavior regarding the purchase of sustainable products. The study was conducted on a sample of 880 respondents in Croatia, Spain, Moldova, Turkey, and Ukraine. The results showed that the quality and composition of products, their origin in bioproduction, and their status as local or healthy products are decisive for the purchase of sustainable products. It was also found that consumers in different countries vary; those in Croatia and Spain have similar criteria and priorities, while those in Moldova, Turkey, and Ukraine differ in certain aspects of their preferences.